2015
DOI: 10.1007/s10461-014-0994-6
|View full text |Cite
|
Sign up to set email alerts
|

Gay Apps for Seeking Sex Partners in China: Implications for MSM Sexual Health

Abstract: Anti-gay stigma and harsh local environments in many low and middle-income countries (LMIC) encourage men who have sex with men (MSM) partner-seeking mobile application (gay app) use. To investigate the sexual risk profiles of gay app users and guide future HIV prevention programs, we conducted a cross-sectional online survey among 1,342 MSM in China examining associations between gay app use and sexual behaviors, including HIV and sexually transmitted disease (STD) testing. Compared to non-app users, app user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 11 publications
(15 reference statements)
14
110
0
5
Order By: Relevance
“…Our results were in line with previous studies assessing samples recruited online or offline [15,16,20,28,[34][35][36][37][38][39][40] that Chinese MSM mostly using Internet to find sex were more likely to be younger, currently single, have higher education, have higher monthly income, engage in condomless receptive anal sex, or have higher odds of being HIV-positive; while less likely to drink alcohol, use alcohol before sex, have sex with women. Our study also uniquely documented that online sex-finding MSM tended to live in the city for longer, being a registered local resident, have health insurance, ever use illicit drugs, or have fewer years in sexual activity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results were in line with previous studies assessing samples recruited online or offline [15,16,20,28,[34][35][36][37][38][39][40] that Chinese MSM mostly using Internet to find sex were more likely to be younger, currently single, have higher education, have higher monthly income, engage in condomless receptive anal sex, or have higher odds of being HIV-positive; while less likely to drink alcohol, use alcohol before sex, have sex with women. Our study also uniquely documented that online sex-finding MSM tended to live in the city for longer, being a registered local resident, have health insurance, ever use illicit drugs, or have fewer years in sexual activity.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that the Internet was the most common venue for Chinese MSM to seek male sexual partners, consistent with findings from previous studies that online AIDS Behav sex-finding has become the predominant mode among MSM in China, as in other countries [15,16,[28][29][30]. China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Subsequent to this, the growing popularity of online sex-seeking and geo-spatial social networking applications has resulted in easy access to high numbers of instantaneous sexual partners. [23][24][25][26][27] Once again, this has increased contact rates between MSM as well as probably of HIV transmission, thereby driving HIV incidence among MSM in recent years.…”
Section: Current Hiv Incidence Data Among Men Who Have Sex With Men Imentioning
confidence: 99%